Perancangan Web Komersial dan Analisis Pengaruhnya Pada UMKM Makanan Kabupaten Boyolali Terhadap Transaksi Penjualan - Budyastomo, Avin Wimar (2086-4221, 2013)
The background of this research is the use of internet or web commercial on micro business at Boyolali district to sell their products. That is why it needs to be studied. Usually people who use web commercial become more creative on business diversification and can penetrate not only local market but also international market.       The purpose of this research is to design web commersial for micro business and analyse calculate the selling transaction. Analytical calculations using paired samples test are used to measure the effect of web commercial. The research’s result is positive increasing of 9,1% on revenues and decrease of marketing expenses by 48,3%. So, it can be concluded that the use of web commercial brings positive effect toward revenue, market cost and selling transaction on snack micro business at Boyolali district.